Милосердя як буттєвий феномен: парадокси величі й змаління (за романами I. Франка) - Матвєєва, Т.С. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2006)
В статье предпринята попытка на материале романистики И. Франко выявить и проанализировать парадоксы проявления милосердия как феномена бытия личности в социально структурированном обществе. The article purposes an attempt at bringing to light and analyzing the paradoxes of showing mercy as a phenomenon of personality's being in a socially structured society out of I. Franko's novels.
Keywords: Франко Іван; милосердя; «Лель і Полель» роман; "Boa constrictor"; "Для домашнього огнища"; "Основи суспільності"